Individualised Professional Development as a Priority Factor in The Formation of Future Professionalism - Artikova, Muhayyo; Kenjaboyev, Sharifjon (Indonesian Journal Publisher, 2024)
Today, increasing the competitiveness of graduates from higher education institutions in the labour market, evaluating the individual professional development of pedagogues, improving diagnostic support, developing student- teachers' professional identities, and implementing the functional tasks of the higher education system based on international and national requirements research are regarded as urgent issues. From this perspective, it is critical to assess student-teachers' individual professional growth in terms of internationalisation of the educational process through advanced overseas experiences and the creation of an innovative educational environment. This article addresses the topics of professional maturity, professional personality and its description, the substance of developing professional characteristics in a future teacher, and the development of professional and pedagogical qualities in a future teacher.